Education on Making Chicken Porridge and Moringa Oleifera Leaves to Prevent Stunting in Mothers PKK Cadres in Pangkalan Jati Cinere Depok - Tiwuk Susantiningsih; Sri Wahyuningsih; Pritha Maya Savitri; Agneta Irmarahayu; Dwi Arwandi Yogi Saputra; Yuni Setyaningsih (Civiliza Publishing, 2026)
Moringa leaves contain bioactive compounds such as flavonoids and polyphenols which have antioxidant and anti-inflammatory properties. The benefits of adding Moringa leaves to chicken porridge as infant formula is that it can enhance the nutritional quality of the porridge, making it a more balanced and complete meal. The protein content from the chicken combined with the vitamins, minerals, and antioxidants from Moringa leaves creates a good synergy for infant growth. Adding Moringa leaves to chicken porridge as infant formula is a smart step to enhance the nutritional value of infant food. The benefits of making Moringa leaf chicken porridge are not yet widely known by the public, so its use for daily consumption is still rare. Therefore, we conducted an educational activity on making moringa leaf chicken porridge for PKK mothers and Posyandu cadres in Pangkalan Jati, Cinere, Depok. This community service initiative involved educating PKK cadres about the benefits of adding Moringa leaves to chicken porridge by providing training on how to make chicken porridge with Moringa leaves, so it can be applied by families and the surrounding community to improve public health and serve as complementary food to enhance breast milk production.